2015
DOI: 10.1097/mca.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Visual scoring of coronary artery calcification in lung cancer screening computed tomography

Abstract: Visual scoring of coronary calcium predicts all-cause and CVD mortality in National Lung Screening Trial participants, independent of current versus former smoking status. Visual coronary calcium scoring in low-dose CT scans helps identify individuals at high risk for mortality who may benefit from further CVD prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The superiority of CAC score over the classical and novel RF has been demonstrated in different populations with several prospective population studies (24)(25)(26)(27)(28). Furthermore, CAC measurement reclassify high risk groups such as diabetic (29)(30)(31)(32)(33), hypertensives (21,(34)(35)(36), elderly (37) and smokers (38,39). Equally important is the absence of CAC which indicates an excellent prognosis in asymptomatic as well in the high risk groups (40)(41)(42) In this group, 52% of men and women were reclassified, all into more accurate risk categories.…”
Section: Cac In Primary Preventionmentioning
confidence: 97%
“…The superiority of CAC score over the classical and novel RF has been demonstrated in different populations with several prospective population studies (24)(25)(26)(27)(28). Furthermore, CAC measurement reclassify high risk groups such as diabetic (29)(30)(31)(32)(33), hypertensives (21,(34)(35)(36), elderly (37) and smokers (38,39). Equally important is the absence of CAC which indicates an excellent prognosis in asymptomatic as well in the high risk groups (40)(41)(42) In this group, 52% of men and women were reclassified, all into more accurate risk categories.…”
Section: Cac In Primary Preventionmentioning
confidence: 97%
“…Finally, we assessed coronary artery calcium using non-ECG-gated CT in SCCOR participants. However, this technique has been validated by multiple independent investigators (18)(19)(20)(21)(22), and results were HeartSCORE cohort, n = 328 Figure 4. Adjusting the association between reduced FEV 1 and increased carotid plaque or coronary artery calcium for endothelial function had no impact (i.e., endothelial function did not explain the association between expiratory airflow and atherosclerosis).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium scores from non-ECG-gated CT have excellent correlation with scores from gated cardiac CT, and independently predict coronary vascular events and mortality (18)(19)(20)(21)(22). Coronary artery calcium was scored using the Weston method (20).…”
Section: Coronary Artery Calciummentioning
confidence: 99%
“…This study suggests that there is benefit to lung cancer screening in other populations as well. Coronary artery calcification is frequently identified in patients undergoing lung cancer screening with LDCT [11][12][13] . NLST data have shown that the presence of coronary artery calcification is associated with a 3 fold increase in cardiovascular death 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification is frequently identified in patients undergoing lung cancer screening with LDCT [11][12][13] . NLST data have shown that the presence of coronary artery calcification is associated with a 3 fold increase in cardiovascular death 12 . These studies suggest a concordance of CAD and lung cancer [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%